Redescription and systematic status of Capillaria philippinensis, an intestinal parasite of human beings - Moravec, F (The Journal of parasitology, 2001)
A redescription of the capillariid originally described as Capillaria philippinensis, a pathogenic intestinal parasite of humans, is provided on the basis of specimens collected in humans in the Philippines. The general morphology, particularly the structure of the male caudal end, shows that this species belongs to Paracapillaria Mendonça, 1963 according to the present classification system of capillariids; the species is transferred to Paracapillaria as Paracapillaria philippinensis (Chitwood, Velasquez, and Salazar, 1968) n. comb. Crossicapillaria n. subgen. is proposed to accommodate this species.
Keywords: Capillaria; Male; parazitární nemoci střev; Animals; lidé; Female; mužské pohlaví; ženské pohlaví; infekce hlísticemi řádu Enoplida; Enoplida Infections; Intestinal Diseases, Parasitic; Humans; zvířata